Načrtovanje novih srednjenapetostnih indikatorjev napetosti s pomočjo izračuna električnega polja - Tičar, Igor (Informacije MIDEM, 2002)
Voltage indicators are used in medium voltage switchgears for indication of voltage presence. They consist of three epoxy insulators with a capacitive voltage dividers, indicator electronic unit, the input of which is connected to the divider's output, LE diode for indication of the presence of voltage and push-button for checking the correctness of indicator's operation. For the voltage indicators that entirely ensure conditions without voltage (shielded invisible parts), the new IEC standards define necessary capacitance, which is much higher than in previously made indicators. This is necessary due to the fact, that for a reliable operation of the voltage indicator to have sufficient electric current. The terminals of voltage indicators that fulfil the above described requirements have be en selected onthe basis of electric field calculations. These calculations have also been used for achieving the most suitable electric field strength distribution. The old version of voltage indicator has been optimised and modified. The concept of a new version has also been developed. For solving 3D electromagnetic problems using finite element method the program package Electromagnetic Field Analysis Tools (EleFAnT3D) has been used. 3D graphical pre-processor enables inputting of 3D structures, boundary conditions, sources and data on materials used. Data input phase is followed by running the computations and presentation of results in graphical and numerical form. The results of electric field calculations and optimisation have shown that for the existing layout of supporting insulatorćs electrodes (Figure 16) the strongest electric field is in the upper part (Figure 12) and oriented towards the outside of insulator (Figure 13). In this part there is also the connection and in the case of voltage increase there is a possibility of a flashover. In the newly designed concept of supporting insulatorćs electrodes (Figure 17) the strongest electric field is in the bottom part (Figure 14), where it almost reaches the dielectric strength of air. Nevertheless, this distribution is more suitable since the electric field is oriented towards the inside of the insulator (Figure 15) - dielectric strength of epoxy is ten times higher than the dielectric strength of air. The calculations of electric field have been verified with measurements on the prototype of the insulators.
Keywords: delilniki napetosti; elektroenergetski sistemi; elektronske enote; indikatorji napetosti